EGYPTIAN POLICY BASED ON INSIGHTS OF HISTORY OF MUSLIM MOVEMENT AND SALAFI MOVEMENT - Ramadhan, Jelang (DIA: Jurnal Administrasi Publik, 2020)
The aftermath of the Arab Spring was leaving a great turnover for many countries as the regime changed, so does Egypt. As one of the most influential countries both in the Middle East and North Africa, Egypt’s domestic politics is quite dynamics since immemorial time, from numerous kingdoms, West colonialism until republic under the authoritarian regime in this modern days. For once, the dynamics of politics itself comes from the grass-root level whichever reached the top such as al-Ikhwan al-Muslimun or Muslim Brotherhood and Salafi Movements which caught people’s attention, not only in Egypt but the entire world. Both basically have religious intentions as it is considered Islamic movements except for their differences in political experience, religious interpretation and manners overpower contestation. Although Egypt currently is controlled by a military coup regime that tends to perpetuate the power, the Brotherhood and Salafi Movements which likewise spread to many countries still lurking and it might be consolidating the power to turn back the democracy to Egyptian who suffer from authoritarian style regime ever since the establishment of the nation after independence from British colonialism. This paper is aimed to describe the policy of the Islamic movement in Egypt which is based on religious intention and the interaction with politics and democratic goal from the nature of establishment, during the Arab Spring and the prospect for Muslim Brotherhood and Salafi Movements as the unrest recently occured.